Fruit Description and Evaluation of Five Treatments to Break Seed Dormancy of Brownlowia peltata Benth. - Noor Rachmadiyanto, Arief; ., Peniwidiyanti; Kusuma Hutabarat, Prima Wahyu (KnE Life Sciences, 2017)
Brownlowia peltata Benth. is a native tree from Borneo, in its germination problem was physical dormancy due to the hard pericarp of the fruit. The study aimed to evaluate five treatments for breaking the seed physical dormancy and the fruit description. The experiment was using Randomized Complete Block Design (RCBD) with four different temperatures of water immersion, a scarification, and control. The fruit of B. peltata was a woody follicle; belong to yellow green group 148 A in color; 29.64 mm in long; 21.62 mm in thickness; 29.86 mm in wide, with an average weight of 12.05 g. Hot water immersion treatment of 40 °C for 60 s; 60 °C for 60 s and 80 °C for 30 s could raise the fruit moisture content of 0.92 % to 1.04 %. There was a significant difference on germination rate coefficient and coefficient of uniformity of germination among treatments. The mature seed does not have a physical dormancy once the carpel splits and create a slit (fruit opening). Keywords: Brownlowia pellata Benth; dormancy; fruit; seed; viability.